Vintage recipes made easy (Taste of Home Books : RDA Enthusiast Brands, LLC, 2025)
Features 285 simplified recipes that allow readers to recreate beloved classic dishes from their childhood, such as roasted chicken and pecan pie, using shorter ingredient lists and modern conveniences, making it easy to evoke nostalgic flavors with minimal preparation time.